Türkiye, NATO and Extended Deterrence - Ali Alkis (CISS Insight Journal, 2025)
This article analyzes Türkiye’s evolving role in the North Atlantic Treaty Organization (NATO)’s nuclear deterrence posture, focusing on its participation in nuclear-sharing arrangements and exercises, such as Steadfast Noon (military exercise). As a member of the Alliance since 1952, Türkiye has played a geostrategically critical role by hosting the United States (US)’ tactical nuclear weapons at Incirlik Air Base and supporting NATO’s collective defence strategy. The study traces the historical trajectory of Türkiye’s nuclear involvement, from Cold War deployments to its current engagement with modernized B61 nuclear bombs and associated readiness activities. It examines the operational contours of Steadfast Noon and the Turkish Air Force’s contributions, particularly through its F-16 fleet. The analysis also addresses key challenges, including Türkiye’s exclusion from the F-35 program, complications in air force modernization, its geopolitical balancing between the US and Russia, and tensions between its commitments to non-proliferation and assertive strategic discourse. The findings show Türkiye’s continued importance to NATO’s southern nuclear posture while highlighting how Ankara’s pursuit of strategic autonomy introduces uncertainties that the Alliance must carefully navigate to maintain deterrence credibility and cohesion.